2013
DOI: 10.1109/jphotov.2012.2209407
|View full text |Cite
|
Sign up to set email alerts
|

>21% Efficient Silicon Heterojunction Solar Cells on n- and p-Type Wafers Compared

Abstract: Abstract-The properties and high-efficiency potential of frontand rear-emitter silicon heterojunction solar cells on n-and p-type wafers were experimentally investigated. In the low-carrierinjection range, cells on p-type wafers suffer from reduced minority carrier lifetime, mainly due to the asymmetry in interface defect capture cross sections. This leads to slightly lower fill factors than for n-type cells. By using high-quality passivation layers, however, these losses can be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
129
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 199 publications
(135 citation statements)
references
References 31 publications
5
129
1
Order By: Relevance
“…The higher surface recombination evident on the p þ surface relative to the n þ is potentially due to c-Si/a-Si:H(i) interface defects exhibiting an electron to hole capture cross section area ratio (r n /r p ) greater than unity. 23 …”
Section: A Interface Passivationmentioning
confidence: 99%
“…The higher surface recombination evident on the p þ surface relative to the n þ is potentially due to c-Si/a-Si:H(i) interface defects exhibiting an electron to hole capture cross section area ratio (r n /r p ) greater than unity. 23 …”
Section: A Interface Passivationmentioning
confidence: 99%
“…With the data for c-Si from Table I, the surface defect density (neglecting the field-effect passivation) results in a surface recombination velocity of 1 cm/s and an effective lifetime of 3.7 ms, consistent with regularly measured lifetimes. 25 ITO was modeled as a conductor that contributed only to the series resistance; we neglected other effects like band bending and band-to-band tunneling. 30 The thickness of the ITO was 65 nm and its mobility and free-carrier concentration are 30 cm 2 /(Vs) and 3 Â 10 20 cm À3 , respectively, giving it a sheet resistance of 107 X/sq.…”
Section: Experimental and Simulationsmentioning
confidence: 99%
“…Such cells would feature an improved blue and red response, be potentially cheaper, and avoid passivation layer damage related to TCO sputtering, 24 compared to our standard devices. 25 When the TCO is absent, the a-Si:H emitter is too resistive to contribute noticeably to the lateral conductivity and has the same role as the insulator in metal-insulatorsemiconductor solar cells of inducing an inversion layer in c-Si. However, while in metal-insulator-semiconductor solar cells, the inversion layer is induced by fixed surface charges, the inversion layer in a-Si:H/c-Si solar cells is a consequence of the a-Si:H emitter doping and the band discontinuities at the interface, introducing new parameters to alter the conductivity of the inversion layer.…”
Section: Introductionmentioning
confidence: 99%
“…14 carrier lifetimes (up to the millisecond range), no light-induced degradation caused by boron-oxygen pair, and high impurity tolerance. [16][17][18][19][20][21] Despite the great success in developing high performance SHJ devices, a large number of photons are still wasted, leading to the significant power loss. It is reported that the total power loss is more than 20% of the current output power.…”
mentioning
confidence: 99%
“…The optical improvement due to the downconversion effect of GQDs gives rise to a high efficiency of 16 for the wavelengths ranging from 300 to 1000 nm.…”
mentioning
confidence: 99%